A Framework for Defining Contextual Features of Training and Coaching Practices. Issue 4 (2nd October 2017) - Meadan, Hedda; Snodgrass, Melinda R.; Palomo, Ilyse; Amenta, Christina G.; Halle, James W.
ABSTRACT: Training and coaching are cited frequently to achieve different goals, by different people, across different fields. Who provides training and coaching and where and how they are provided may influence the effectiveness of the training and coaching efforts, making the clear identification of these contextual features of paramount importance to successful implementation and dissemination of training and coaching programs. First, we propose a framework for elucidating these contextual features, and then we apply this framework to a circumscribed review of the literature on parent training and coaching in early intervention services to assess its utility. We discuss the extent to which contextual features have been described in this body of research, offer additional considerations for applying the framework based on this review, and propose possible implications of our findings for implementation, dissemination, and future research efforts.